Effect of seat belt use on road accidents in Thailand - Nuttapong Boontob (2018)
This research was conducted to investigate the factors influencing seat belt use in Thailand. An additional aim was to analyze the effect of seat belt use in motor vehicle crashes with the use of injury data from hospitals. Significant factors influencing seat belt use were determined through field observations and a questionnaire survey. Seat belt use was observed to be higher in passenger cars than in pickups; lower seat belt use was observed for females, and drivers' use of seat belts was considerably higher than that of front seat passengers and passengers in the rear seat position. Statistical analysis from the questionnaire survey found that the sex, age, education, income, vehicle type, seating position, seat belt installation, and average travel time and the interaction between age and seating position, education and income, and vehicle type and seating position significantly affect seat belt use. Probability of survival and severity index analysis found that unbelted car users could have a severity rate 67.5% higher than those who are belted. From the odds ratio analysis, car users who are unbelted have a higher fatality risk than those who are belted, as shown in the odds ratio 1.54. Fatality reduction analysis shows that with seat belt use, 35 of every 100 crash fatalities could be prevented. This study shows that by maximizing seat belt use, lives lost due to road crash injuries could be reduced annually.